Sacha inchi (Plukenetia volubilis) seed oil alleviates Plasmodium berghei infection in mice by reducing proinflammatory cytokine levels and inhibiting parasite growth - Rizky Setia Firdaus; Nadiah Farah Fadilah; Lucia Tri Suwanti; Heny Arwati; Heni Puspitasari (Open Veterinary Journal)
Abstract: Sacha inchi (Plukenetia volubilis) seed is a rich source of polyunsaturated fatty acids (PUFA), namely omega-3 and omega-6, which provide various health benefits, especially in the prevention of inflammatory diseases. Malaria, caused by Plasmodium species, triggers inflammasome activation, leading to the release of proinflammatory cytokines.